STRATEGY ANALYSIS OF BPRS BHAKTI SUMEKAR PRAGAAN PRIMARY BRANCH OFFICE IN OVERCOMING NON PERFORMING FINANCING (NPF) IN MURÄ€BAá¸¤AH FINANCING PRODUCTS - Supriyadi Supriyadi; Ahmad Taufik (Masyrif : Jurnal Ekonomi, Bisnis dan Manajemen, 2023)
Non performing financing or often known as Non Performing FinancingÂ (NPF) is a credit or financing that has been disbursed but is less current, doubtful, and bad.Â NPF is one of the key indicators to assess the performance of bank functions, because if the NPF is high, the bank is indicated to have failed in managing bank performance, which is above 5% according to POJK Number 15/POJK.03/2017.Â BPRS Bhakti Sumekar Pragaan Primary Branch Office has an NPF of 6% with 73 number of customers who have problems with murÄbaá¸¥ah financing products.Â This study aims to determine the factors influencing NPF and BPRS Bhakti Sumekar strategy of Pragaan Primary Branch Office in overcoming NPF in murÄbaá¸¥ah financing products In this study, researchers used descriptive qualitative, because they wanted to describe the facts through primary and secondary data as well as interview results about bank strategies in overcoming Non Performing FinancingÂ (NPF) at BPRS Bhakti Sumekar Pragaan Primary Branch Office.Â The results of the study, the factors that cause the occurrence of NPF include internal factors and external factors.Â Internal factors occur due to the bank's lack of optimality in analyzing potential customers.Â While the second factor is external factors which are divided into two factors, namely customer factors and environmental factors.Â That way the strategy used is different;Â First, billing intensely with a persuasive approach.Â Second, warnings in the form of warning letters and auction letters.Â Third, apply the 3Â R (Rescheduling, Reconditioning, Restructurization) such as reducing installments by increasing the maturity period of payment.Â Fourth, the auction of customer guarantees that result in default.